2012
DOI: 10.1186/1471-2164-13-105
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational and magnetic field variations synergize to cause subtle variations in the global transcriptional state of Arabidopsis in vitro callus cultures

Abstract: BackgroundBiological systems respond to changes in both the Earth's magnetic and gravitational fields, but as experiments in space are expensive and infrequent, Earth-based simulation techniques are required. A high gradient magnetic field can be used to levitate biological material, thereby simulating microgravity and can also create environments with a reduced or an enhanced level of gravity (g), although special attention should be paid to the possible effects of the magnetic field (B) itself.ResultsUsing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 43 publications
(57 reference statements)
10
39
0
Order By: Relevance
“…Similar to our results, transcriptome analysis in Arabidopsis exposed to gravity stimulation also revealed that metabolism is one of major gene groups responding to gravitropism (Kimbrough et al 2004;Kittang et al 2004) Among the metabolism pathways identified in this study, energy metabolism was also found to function in plants under gravitropic stimulation according to proteomic analysis (Azri et al 2009;Herrera et al 2010). In Arabidopsis, secondary metabolism genes were altered by magnetically induced hyperand microgravity at both transcription and translation levels (Manzano et al 2012;Herranz et al 2013). Proteome analysis of poplar stems exposed to gravitropic stimulation has led to determination of several pathways also identified in our study, including nucleotide metabolism, carbohydrate metabolism, photosynthesis and primary metabolism (energy) (Azri et al 2009).…”
Section: Discussionsupporting
confidence: 86%
“…Similar to our results, transcriptome analysis in Arabidopsis exposed to gravity stimulation also revealed that metabolism is one of major gene groups responding to gravitropism (Kimbrough et al 2004;Kittang et al 2004) Among the metabolism pathways identified in this study, energy metabolism was also found to function in plants under gravitropic stimulation according to proteomic analysis (Azri et al 2009;Herrera et al 2010). In Arabidopsis, secondary metabolism genes were altered by magnetically induced hyperand microgravity at both transcription and translation levels (Manzano et al 2012;Herranz et al 2013). Proteome analysis of poplar stems exposed to gravitropic stimulation has led to determination of several pathways also identified in our study, including nucleotide metabolism, carbohydrate metabolism, photosynthesis and primary metabolism (energy) (Azri et al 2009).…”
Section: Discussionsupporting
confidence: 86%
“…In general, data obtained from cell cultures reveal alterations in cell growth and proliferation that could be compared to those found in seedlings, indicating that a significant part of the response to altered gravity does not depend on specialized cells containing mechanoreceptors (Manzano et al, 2012a;Herranz et al, 2013). In cell cultures we verified (i) the alteration of the relative proportion of cell cycle phases (which probably leads to a change in the duration of the cycle), (ii) the change in expression of numerous genes acting as regulators in cell cycle checkpoints of phase transitions, and (iii) the deregulation of ribosome biogenesis by means of the alteration of nucleolar structure and of transcriptional and post-translational changes of key proteins of this process, such as nucleolin and fibrillarin.…”
Section: Arabidopsis Thaliana-cell Growth and Proliferationmentioning
confidence: 95%
“…In addition to the work carried out with seedlings, solid in vitro cell cultures of Arabidopsis thaliana were used and exposed to the HFML magnet (maximum field of 16.5 T from 0g* to 2g*), the RPM (real random mode), and the LDC (2g, hypergravity), as a homogeneous proliferating cellular material with the use of agar-filled tubes/plates of the required size (Manzano et al, 2012a). This material has been rarely used in real spaceflight experiments (Paul et al, 2012), but its use as source material for altered gravity research has the purpose of testing whether cells not specialized in gravity perception respond to gravity alteration.…”
Section: Arabidopsis Thaliana-cell Growth and Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, in both plant and animal cells it has been reported the perception of mechanical signals by cells not apparently specialized in gravity sensing [20][21][22] and, in several laboratories, different research groups, including us, have reported genomic and proteomic effects of an altered gravity environment (even of spaceflight) on Arabidopsis callus cell cultures. [23][24][25][26][27] In the case of the magnetic levitation, the response at the meristematic cell level is associated to an altered polar auxin transport; this means that there should be an intermediate factor capable of linking the signal sensed in the cell by the diamagnetic levitation of water and the alteration of the polar auxin transport. In turn, cell cultures lack both, gravitropic signals induced by statolith movements and polar auxin transport However, gravity alteration is sensed by cells and results in cellular and molecular effects, also including disruption of meristematic competence (unpublished results).…”
Section: The Complex Mechanism Of Transduction Of Gravity Mechanosignmentioning
confidence: 99%